2014
DOI: 10.1007/s12665-014-3276-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of injected CO2 on geochemical alteration of the Altmark gas reservoir in Germany

Abstract: Capturing CO2 from point sources and storing it into geologic formations is a potential option to allaying the CO2 level in the atmosphere. In order to evaluate the effect of geological storage of CO2 on rock-water interaction, batch experiments were performed on sandstone samples taken from the Altmark reservoir, Germany, under insitu conditions of 125°C and 50 bar CO2 partial pressure. Two sets of experiments were performed on pulverized sample material placed inside a closed batch reactor in a) CO2 saturate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In former experimental studies on plugs of the Altmark reservoir sandstones the dissolution of carbonate and anhydrite, accompanied by an increase in rock porosity and permeability was already shown (Huq et al 2014;Pudlo et al 2012). This is confirmed by the decrease of Ca The distinct behavior of anhydrite (and carbonate) in the presence of pure CO 2 and CO 2 -SO 2 mixtures during laboratory experiments is described by, e.g., Kummerow Fig.…”
Section: Discussionmentioning
confidence: 90%
“…In former experimental studies on plugs of the Altmark reservoir sandstones the dissolution of carbonate and anhydrite, accompanied by an increase in rock porosity and permeability was already shown (Huq et al 2014;Pudlo et al 2012). This is confirmed by the decrease of Ca The distinct behavior of anhydrite (and carbonate) in the presence of pure CO 2 and CO 2 -SO 2 mixtures during laboratory experiments is described by, e.g., Kummerow Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Bowker et al, 1991;Emberly et al, 2005;Assayag et al, 2009) and in laboratory experiments (e.g. Berrezueta et al, 2013;Huq et al, 2014;Pudlo et al, 2015) with consequences reported on the permeability (Sayegh et al, 1990;Pudlo et al, 2015;Yasahura et al, 2015) and elastic/mechanical properties of the host rock (Daley et al, 2007;Oikawa et al, 2008;Zheng et al, 2015;Delle Piane and Sarout, submitted).…”
Section: Fluid-rock Interaction and Resulting Permeability Degradationmentioning
confidence: 99%